2018
DOI: 10.1111/cobi.13161
|View full text |Cite
|
Sign up to set email alerts
|

Great Barrier Reef recovery through multiple interventions

Abstract: The decline of coral cover on Australia's Great Barrier Reef (GBR) has largely been attributed to the cumulative pressures of tropical cyclones, temperature-induced coral bleaching, and predation by crown-of-thorns starfish (CoTS). In such a complex system, the effectiveness of any management intervention will become apparent only over decadal time scales. Systems modeling approaches are therefore essential to formulating and testing alternative management strategies. For a network of reefs, we developed a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 43 publications
1
56
0
Order By: Relevance
“…Most of these records, however, comprise predation on injured and moribund or dead individuals under experimental conditions, with only a limited number of field observations of predation on early life stages and on healthy, un-injured adults 16 . Despite this lack of field observations of CoTS predation, several independent modelling studies have provided support for the 'predator removal' hypothesis [17][18][19] . Hence, a more comprehensive understanding of coral reef organisms that prey on live CoTS in the field, including on early life stages, is critical to inform active intervention in predation pressure to mitigate CoTS population outbreaks.…”
mentioning
confidence: 99%
“…Most of these records, however, comprise predation on injured and moribund or dead individuals under experimental conditions, with only a limited number of field observations of predation on early life stages and on healthy, un-injured adults 16 . Despite this lack of field observations of CoTS predation, several independent modelling studies have provided support for the 'predator removal' hypothesis [17][18][19] . Hence, a more comprehensive understanding of coral reef organisms that prey on live CoTS in the field, including on early life stages, is critical to inform active intervention in predation pressure to mitigate CoTS population outbreaks.…”
mentioning
confidence: 99%
“…In conclusion, we found that split spawning events could increase the robustness of larval supply to coral reefs. Such considerations may increase in importance as the GBR faces an increasingly uncertain future of escalating intensity and severity of disturbances 6,43,5659 . Allee effects may become more frequent as densities of coral populations decline, exacerbating potential reproductive costs of split spawning.…”
Section: Discussionmentioning
confidence: 99%
“…As we outline above, nested network approaches are also helping to link understanding of interactions and connectivity across processes, space, and time (Pilosof et al, 2017). As an example, to support management of the deleterious impacts of crown of thorns starfish on Australia's Great Barrier Reef coral communities, ecological models are being integrated across a range of scales accounting for finescale Allee effects (Rogers et al, 2017) through to embedding an ecological model in a meta-community reef network model incorporating large scale processes such as cyclone and terrestrial runoff from agriculture practices (Condie et al, 2018).…”
Section: Gaps In Fundamental Ecological Understandingmentioning
confidence: 99%